Loneliness enhances brand love for individualistic (but not collectivistic) consumers - Ng, Andy H. (Frontiers in Psychology, 2025)
IntroductionIt is not uncommon for people to experience loneliness. When people feel lonely, they are motivated to reestablish connections with other people directly or restore a sense of social connection indirectly through other means. As a brand symbolically connects all people affiliated with the same brand, constituting a broad social group, loneliness may motivate people to enhance their emotional attachment to a brand (i.e., brand love) to restore a sense of social connection indirectly through the brand. In the current research, I adopt a cultural lens to examine this proposition.MethodsAcross two studies (Study 1: N = 200; Study 2: N = 267), I examined the moderating effect of culture on the causal effect of loneliness on brand love. Loneliness was manipulated using a recall task, and culture was measured and operationalized as individual differences in cultural orientation (Study 1) and racial background (Study 2).ResultsFor both studies, results indicated that culture moderated the effect of loneliness on brand love, such that loneliness caused an increase in brand love for individualistic consumers, but not collectivistic consumers.DiscussionThese findings are consistent with current theorizing and empirical findings about cultural differences in how people conceptualize ingroup and relate to strangers who belong to the same broad social group.